Influence des activités agricoles sur la végétation le long d’un gradient pluviométrique nord-sud du Burkina Faso - Massouroudini Akoudjin; Sébastien Kiéma; Mamadou Sangare; Jean César; Jérémy Bouyer; Chantal Kabore-Zoungrana (VertigO)
Evaluation of the ecological state of Burkina Faso landscapes is necessary to understand human action on environment. This study aimed at characterizing the study sites to understand interactions between climate, humans and ecosystems along a rainfall gradient. The study was carried out along anthropic gradients overlapping protected areas, cropping areas and grazing areas in four agro-sylvo-pastoral areas of Burkina Faso. Floristic inventories were conducted at ecological surveys sites, according to an itinerant inventory method. The floristic richness is decreasing along the rainfall gradient and anthropic gradients. Correspondence analysis of floristic surveys allowed us separating the sahelian to savannah area and representing three types of landscapes (protected, cropping and grazing areas) in each zone based on land use, thus proving human impacts on ecosystem. Human action and climate aridity seems to have the same effect on vegetation. Grazing areas appear as intermediate ecology zones between cropping areas and protected areas.